Chemical contaminant levels in edible seaweeds of the Salish Sea and implications for their consumption - Hahn, Jennifer L; Van Alstyne, Kathryn L; Gaydos, Joseph K; Wallis, Lindsay K; West, James E; Hollenhorst, Steven J; Ylitalo, Gina M; Poppenga, Robert H; Bolton, Jennie L; McBride, David E; Sofield, Ruth M (PLOS ONE, 2022)
Despite growing interest in edible seaweeds, there is limited information on seaweed chemical contaminant levels in the Salish Sea. Without this knowledge, health-based consumption advisories can not be determined for consumers that include Tribes and First Nations, Asian and Pacific Islander community members, and recreational harvesters. We measured contaminant concentrations in edible seaweeds (Fucus distichus, F. spiralis, and Nereocystis luetkeana) from 43 locations in the Salish Sea. Metals were analyzed in all samples, and 94 persistent organic pollutants (POPs) (i.e. 40 PCBs, 15 PBDEs, 17 PCDD/Fs, and 22 organochlorine pesticides) and 51 PAHs were analyzed in Fucus spp. We compared concentrations of contaminants to human health-based screening levels calculated from the USEPA and to international limits. We then worked with six focal contaminants that either exceeded screening levels or international limits (Cd, total Hg, Pb, benzo[a]pyrene [BaP], and PCBs) or are of regional interest (total As). USEPA cancer-based screening levels were exceeded in 30 samples for the PCBs and two samples for BaP. Cadmium concentrations did not exceed the USEPA noncancer-based screening level but did exceed international limits at all sites. Lead exceeded international limits at three sites. Because there are no screening levels for total Hg and total As, and to be conservative, we made comparisons to methyl Hg and inorganic As screening levels. All samples were below the methyl Hg and above the inorganic As screening levels. Without knowledge of the As speciation, we cannot assess the health risk associated with the As. While seaweed was the focus, we did not consider contaminant exposure from consuming other foods. Other chemicals, such as contaminants of emerging concern (e.g., PFAS, pharmaceuticals and personal care products), should also be considered. Additionally, although we focused on toxicological aspects, there are cultural and health benefits of seaweed use that may affect consumer choice.